Sanitation Pattern and its Impact on Child in Relation to their Diarrheal Disease of two Upazilla under Satkhira District - Huda, N; Islam, MA; Hasan, M; Hossain, MR (Journal of Environmental Science and Natural Resources, 2022)
The sanitation pattern is not so good in rural areas of Bangladesh. About 2.2 million children died of diarrhea disease around the world and these deaths represent approximately 15% of all child deaths under the age of five in developing countries. For this study, two rural areas of Satkhira District of Bangladesh were selected. The information was collected from households that had children under 5 years old. The majority of the locals are illiterate and impoverished. They have a low income and are not well aware of sanitation and children’s diarrhea. Most people use tubewell water for drinking purposes and others use ponds, rivers and hand pump water for domestic purposes. Water, sanitation, and hygiene interventions reduce diarrheal disease on average by between one-quarter and one-third. New sanitary solutions are required, and the process of acquiring latrines and sewers must be facilitated and supported both legislatively and financially. Public authorities must continue to be responsible for the provision of water that is free of fecal contaminants. In the private domain, hygiene promotion should focus on the elimination of human stools from the domestic environment. We should ensure safe sanitation, clean water and a hygienic environment for children and their survival. Environ. Sci. & Natural Resources, 13(1&2): 100-109, 2020